Mechanics of standing and crouching sprint starts - Slawinski, J.; Houel, N.; Bonnefoy-Mazure, A.; Lissajoux, K.; Bocquet, V.; Termoz, N. (Journal of Sports Sciences, 2017)
The aim of this study was to compare the kinetic and kinematic parameters of standing and crouch sprint starts. Parallel starts (PS), false starts (FS), jump starts (JS) and crouch starts (3PS) were compared. Eighteen participants performed each start on a force plate and six infrared cameras captured the three-dimensional coordinates of 36 retro-reflective markers. Performance during a five-metre sprint (T5m) was analysed. Duration of the start phase (Tstart), mean values of horizontal and total ground reaction forces (GRFs) (Fx_mean and Ftot_mean), ratio of force (RF), maximal power (Pmax) and kinetic energy (KE) of each limb were calculated. Significant differences were found for T5m, Tstart, KE, Pmax, Fx_mean, Ftot_mean and RF for the crouch start compared to the other starts (P = 0.05). Significant correlations were found between T5m and Tstart (r = 0.59; P = 0.001), and T5m and Pmax, Fx_mean and RF (-0.73 = r = -0.61; P = 0.001). To conclude, the crouch start resulted in the best performance because Tstart was shorter, producing greater Pmax, Fx_mean with a more forward orientation of the resultant force. Greater KE of the trunk in each start condition demonstrated the role of the trunk in generating forward translation of the centre of mass (CM).